Substrates and fertilization in the development of São Carlos grass - Dias, J. A. C.; Santos, P. L. F.; Gazola, R. P. D.; Saraiva, B. C.; Castilho, R. M. M. (Scientific Electronic Archives, 2018)
Â SÃ£o Carlos grass (Axonopus affinis) is recommended for use in industrial areas, residential gardens and country houses, and has tolerance to semi-shaded areas. The experiment was carried out at UNESP, Campus de Ilha Solteira - SP, in the period from 06/28 to 12/14/2014, in a greenhouse (Pad & Fan, mean temp 25Â°C and average luminosity 2500 lux). The grass was implanted in black plastic containers (8.46 liters), and the experimental design was a 3x4 factorial composed of three substrates: soil, soil + organic matter (1: 1) and soil + organic matter + sand (2:1:1), and three chemical fertilizers: Forth JardimÂ®, Maxgreen S2Â® and NPK (10-10-10), and without fertilization. The organic matter showed a beneficial effect on the development of the turfgrass, as well as the use of Forth JardimÂ®.